Application of microbial immobilization on chitosan composite membrane for manganese removal in water treatment. (14th March 2022) - Song, Wenyan; Huang, Tianfeng; Zuo, Huajiang; Deng, Dongmei; Tang, Chunyi
Abstract: Environmentally friendly natural materials, chitosan (CS) and tannic acid (TA), were used to prepare a composite membrane and immobilize Stenotrophomonas maltophilia on it, which was then applied for removing manganese in water. Surface morphology was investigated, and the amount of immobilized fungus on the composite membrane was probed using scanning electron microscopy (SEM). A composite membrane was prepared by grafting CS and TA on a cotton cloth, and the experimental conditions were optimized; preferential immobilization of S. maltophilia on the composite was achieved. A Mn 2+ standard calibration curve was obtained via atomic absorption spectroscopy; the removal of manganese ions was determined and compared before and after immobilization on the composite membrane. For glutaraldehyde concentration of 8%, solution pH of 5, TA concentration of 0.05 g/mL, and temperature of 80 °C, the grafting of the TA/CS composite membrane was the best, resulting in better immobilization of S. maltophilia . SEM images showed that a large number of S. maltophilia were immobilized on the composite membrane, substantially improving the manganese removal performance. The removal rate of the manganese ions was the best and reached >70% for solution pH of 5 and Mn 2+ concentration of 0.6–1.2 mg/L. Graphical abstract: A composite membrane was prepared by grafting CS and TA on a cotton cloth, and the experimental conditions were optimized; preferential immobilization of S. maltophilia on the composite was achieved. A Mn 2+ standard calibration curve was obtained via atomic absorption spectroscopy; the removal of manganese ions was determined and compared before and after immobilization on the composite membrane. Image 1 Highlights: An important addition in the area of wastewater treatment for removal rate of Mn 2+ . High removal rate of Mn 2+ up to 70%. The innovation reported concerning the use of composites with immobilized microorganisms as a potential adsorbent.